Influence of hydrothermal time on structural properties of ZnO nanorods grown on spin-coated ZnO seeding layer - Hambalee Mahamu; Wuttichai Srinonate; Wisanu Pecharapa (My University, 2019)
Abstract Most of the recent nanodevices are fabricated by using high-efficiency deposition methods and patterned via high-resolution lithography. However, there are drawbacks for the methods including small-scale product, high cost consumption, and multi-step processes. To reduce these disadvantages, this work focuses on the usage of sol-gel synthesis and spin coating method to fabricate ZnO seed layer onto glass substrates. All of substrates were patterned by conventional UV photolithography at exposure time of 7 seconds, then ZnO nanorods were hydrothermally grown at 90°C for 2, 3, and 4 hours, respectively. All of samples were characterised by scanning electron microscope (SEM) which revealed the sharp and smooth tip hexagonal structure at different hydrothermal time. The evolution of the nanorods’ growth was investigated, and the diameters were estimated. Moreover, crystal quality was revealed by x-ray diffractograms. It was clear that the domination of c-axis plane occurred for all the samples associates with the crystallinity of the nanostructures. This indicated escalating of the non-monodirectional growth plane in increasing nanorods’ diameter as the nanorods are polycrystal. Furthermore, the optical properties of the samples were observed by UV-visible spectroscopy and photoluminescence technique (PL). UV-visible spectroscopic data showed diminishing of the energy band gap when the diameter grew up. PL data revealed the reduction of the intensity ratio at near-band-edge peak versus oxygen vacancy peak. This information pointed to the decreasing trend of the crystal quality with escalating growth time.
Keywords: Nanorod; Spin Coating; ZnO doping and properties